2021
DOI: 10.3389/fpls.2020.597554
|View full text |Cite|
|
Sign up to set email alerts
|

Morphophysiology of Potato (Solanum tuberosum) in Response to Drought Stress: Paving the Way Forward

Abstract: The cultivated potato (Solanum tuberosum L.) is currently the third most important food crop in the world and is becoming increasingly important to the local economies of developing countries. Climate change threatens to drastically reduce potato yields in areas of the world where the growing season is predicted to become hotter and drier. Modern potato is well known as an extremely drought susceptible crop, which has primarily been attributed to its shallow root system. This review addresses this decades old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 141 publications
(302 reference statements)
0
54
0
Order By: Relevance
“…Although potato plants are susceptible to water stress and the decrease in available soil moisture, the plants presented a significant partial stomatal closure at the most stressed irrigation levels implemented. This response could vary due to the morphophysiological features of the different potato genotypes/cultivars [76]. Thus, Sun et al [77] found that stomatal morphology in potato leaves has plasticity to soil moisture status and dynamics changes.…”
Section: Stomatal Resistance Patterns Under Irrigation Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although potato plants are susceptible to water stress and the decrease in available soil moisture, the plants presented a significant partial stomatal closure at the most stressed irrigation levels implemented. This response could vary due to the morphophysiological features of the different potato genotypes/cultivars [76]. Thus, Sun et al [77] found that stomatal morphology in potato leaves has plasticity to soil moisture status and dynamics changes.…”
Section: Stomatal Resistance Patterns Under Irrigation Levelsmentioning
confidence: 99%
“…Although potato plants are susceptible to water stress and the decrease in available soil moisture, the plants presented a significant partial stomatal closure at the most stressed irrigation levels implemented. This response could vary due to the morphophysiological features of the different potato genotypes/cultivars [76]. Thus, Sun et al [77] found that stomatal morphology in potato leaves has plasticity to soil moisture status and For the 2018/2019 season, the potato plant presented the lowest resistance to loss of water during midday time (12:00-14:00) with average r st values of 43, 48, and 60 s m −1 for IL 1 , IL 2 , and IL 3 , respectively, whereas average r st values of 50, 54, and 65 s m −1 for IL 1 , IL 2 , and IL 3 were observed during the 2019/2020 season, respectively.…”
Section: Stomatal Resistance Patterns Under Irrigation Levelsmentioning
confidence: 99%
“…Therefore, potato improvement for drought tolerance and implementation of irrigation systems in this crop is essential to obtain marketable yields and avoid the risk of failure of the crop in years with low precipitation. The situation will probably be more pronounced in the future, given the trends in the last decades (Raymundo et al, 2014;Aliche et al, 2019;Hill et al, 2021). These results exemplify how much we can lose in productivity in dryland conditions even in one of the most favorable areas for growing potatoes globally and how risky this situation can be for the performance of the potato farms in the future.…”
Section: Discussion Tuber Yield Productivity Under Irrigation Vs Rainfed Conditionsmentioning
confidence: 93%
“…The underground part of the plant (the root system), in addition to providing a site for fixation and water and nutrient uptake, plays a significant role in evolving abiotic stress responses [17,53]. Prolonged drought can induce adaptive responses in plants, and it can be manifested by modified structure and function of roots [53], which can play an important role in coping with water stress [19,35,55].…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that there may be large differences between species and cultivars in drought stress responses, and even variability has been found in the susceptibility of potato cultivars [15,16]. Several experiments were performed to identify traits that could be related to drought stress and to select genotypes with the desired characters in several crops [4,17] including potatoes [18][19][20]. Some of these traits can also be detected at the cellular and/or tissue level, such as the adjustment of osmotic pressure, which can be tested/modelled under laboratory conditions [21] or even in vitro [22,23].…”
Section: Introductionmentioning
confidence: 99%